Guided Peer Tutoring and the Development of Motor Abilities by Children with Dyspraxia in Buea of the South West Region of Cameroon - El-Aldrien, Munge Nzume; Shey, Patrick Fonyuy (Journal of Research in Innovative Teaching and Inclusive Learning, 2024)
This study sought to examine the effect of guided peer tutoring and the development of motor abilities by children with dyspraxia in Buea of the South West Region of Cameroon. The research design adopted for this study was the experimental design and the type was the quasi-experimental since the participants of the study were not randomised. The type of quasi-experimental design adopted for the study was a comparative pre-test post-test design with non-randomized experimental and control groups. The purposive sampling technique was also used to select the sample for the study. The sample size was twenty-four (24) class four pupils with dyspraxia between ages 8-10 selected from two schools (Presbyterian School (P.S) Bomaka and Catholic School (C.S) Bolifamba) in the Buea Municipality. Both quantitative (motor ability test for pupils) and qualitative (interview guide for teachers) methodologies were used to collect data for the study. Descriptive statistical techniques were used to analyse the data collected from the field. Qualitative data were analysed using thematic approach whereby ideas or viewpoints were grouped under umbrella terms of key concepts. The quantitative data were subjected to inferential statistical analysis using Statistical Package of the Social Sciences (SPSS) version 21.0. The major results obtained were that the use of guided peer tutoring for pupils with dyspraxia enhanced the development of their motor abilities (in areas of strength, balance, coordination (gross motor skills) and fine motor skills (writing, drawing, cutting, lacing, buttoning, clapping and bouncing). Hence it is recommended that children with dyspraxia should be allowed to freely interact with their normal peers during lessons and play. During such moments, teachers can pair pupils with dyspraxia with other pupils so as to facilitate the development of motor skills through peer mentoring and interaction.